The intrinsic and extrinsic effects of TET proteins during gastrulation - Cheng, Saifeng; Mittnenzweig, Markus; Mayshar, Yoav; Lifshitz, Aviezer; Dunjić, Marko; Rais, Yoach; Ben-Yair, Raz; Gehrs, Stephanie; Chomsky, Elad; Mukamel, Zohar; Rubinstein, Hernan; Schlereth, Katharina; et al. (Cell, 2022)
Mice deficient for all ten-eleven translocation (TET) genes exhibit early gastrulation lethality. However, separating cause and effect in such embryonic failure is challenging. To isolate cell-autonomous effects of TET loss, we used temporal single-cell atlases from embryos with partial or complete mutant contributions. Strikingly, when developing within a wild-type embryo, Tet-mutant cells retain near-complete differentiation potential, whereas embryos solely comprising mutant cells are defective in epiblast to ectoderm transition with degenerated mesoderm potential. We map de-repressions of early epiblast factors (e.g., Dppa4 and Gdf3) and failure to activate multiple signaling from nascent mesoderm (Lefty, FGF, and Notch) as likely cell-intrinsic drivers of TET loss phenotypes. We further suggest loss of enhancer demethylation as the underlying mechanism. Collectively, our work demonstrates an unbiased approach for defining intrinsic and extrinsic embryonic gene function based on temporal differentiation atlases and disentangles the intracellular effects of the demethylation machinery from its broader tissue-level ramifications.
Gesehen am 26.10.2022